2007
DOI: 10.1016/j.adolescence.2006.11.009
|View full text |Cite
|
Sign up to set email alerts
|

Parenting styles, coping strategies, and the expression of homesickness

Abstract: The present study examined the role of parenting styles in the experience and expression of homesickness, and the way of coping with the feelings involved. Using a sample of 670 first year college and university students, aged 16 to 25, we tested three hypotheses: (1) authoritarian, permissive as well as uninvolved parenting are associated with the experience of homesickness, contrary to students with authoritative parents who are less likely to have feelings of homesickness; (2) students with authoritarian, p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
46
2
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 62 publications
(55 citation statements)
references
References 24 publications
6
46
2
1
Order By: Relevance
“…Our perspective considers parents as models of self-control, social skills, engagement in learning, and healthy lifestyles (Uusiautti, K. Määttä, & M. Määttä, 2013;see also Hubbs-Tait, 2008;Nijhof & Engels, 2007;Veríssimo et al, 2011), and providers of the sense of "worthy of love" in children (Lawrence, 2001). The purpose is not to set pressure to parents and demand ideal parenting from all.…”
Section: Resultsmentioning
confidence: 99%
“…Our perspective considers parents as models of self-control, social skills, engagement in learning, and healthy lifestyles (Uusiautti, K. Määttä, & M. Määttä, 2013;see also Hubbs-Tait, 2008;Nijhof & Engels, 2007;Veríssimo et al, 2011), and providers of the sense of "worthy of love" in children (Lawrence, 2001). The purpose is not to set pressure to parents and demand ideal parenting from all.…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, children with permissive and indifferent parents are more likely to experience symptoms of depression than children whose parents are authoritative or authoritarian (Nijhof & Engels, 2007). Similarly, it has also been found that children whose parents are uninvolved often exhibit low signs of independence (Shaffer, 2000).…”
Section: Uninvolved Parentingmentioning
confidence: 99%
“…Authoritarian parenting has been found to correlate with lower levels of self confidence and a lower ability to employ effective coping mechanisms among adolescents (Nijhof & Engels, 2007). Research has also found a correlation between the restrictive and hostile characteristics of authoritarian parenting and high levels of adolescent anxiety because the child often externalizes hislher problems (Nijhof & Engels, 2007).…”
Section: Authoritarian Parentingmentioning
confidence: 99%
See 2 more Smart Citations